How do consent forms for diagnostic high‐throughput sequencing address unsolicited and secondary findings? A content analysis. Issue 3 (8th July 2018) - Vears, D.F.; Niemiec, E.; Howard, H.C.; Borry, P.
Abstract : Graphical representation of the categories and subcategories identified in the forms. † Value includes 13 forms that did not mention unsolicited findings (UF) and/or secondary findings (SF). Abstract : Whole exome and whole genome sequencing are increasingly being offered to patients in the clinical setting. Yet, the question of whether, and to what extent, unsolicited findings (UF) and/or secondary findings (SF) should be returned to patients remains open and little is known about how diagnostic consent forms address this issue. We systematically identified consent forms for diagnostic genomic sequencing online and used inductive content analysis to determine if and how they discuss reporting of UF and SF, and whether patients are given options regarding the return of these results. Fifty‐four forms representing 38 laboratories/clinics were analyzed. A quarter of the forms did not mention UF or SF. Forms used a variety of terms to discuss UF and SF, sometimes using these interchangeably or incorrectly. Reporting policies for UF varied: 5 forms stated that UF will not be returned, 15 indicated UF may be returned, and 28 did not specify their policy. One‐third indicated their laboratory returns SF. Addressing inconsistent terminology and providing sufficient information about UF/SF in consent forms will increase patient understanding and help ensure adequate informed consent.